Does time to surgery affect patient-reported outcome in proximal humeral fractures? A subanalysis of the PROFHER randomized clinical trial. (January 2020) - Norman, John G.; Brealey, Stephen; Keding, Ada; Torgerson, David; Rangan, Amar
Abstract : Aims: The aim of this study was to explore whether time to surgery affects functional outcome in displaced proximal humeral fractures Methods: A total of 250 patients presenting within three weeks of sustaining a displaced proximal humeral fracture involving the surgical neck were recruited at 32 acute NHS hospitals in the United Kingdom between September 2008 and April 2011. Of the 125 participants, 109 received surgery (fracture fixation or humeral head replacement) as per randomization. Data were included for 101 and 67 participants at six-month and five-year follow-up, respectively. Oxford Shoulder Scores (OSS) collected at six, 12, and 24 months and at three, four, and five years following randomization was plotted against time to surgery. Long-term recovery was explored by plotting six-month scores against five-year scores and agreement was illustrated with a Bland-Altman plot. Results: The mean time from initial trauma to surgery was 10.5 days (1 to 33). Earlier surgical intervention did not improve OSS throughout follow-up, nor when stratified by participant age (< 65 years vs ≥ 65 years) and fracture severity (one- and two-part vs three- and four-part fractures). Participants managed later than reported international averages (three days in the United States and Germany, eight days in the United Kingdom) did not have worse outcomes. At five-year follow-up, 50 participants (76%) had the same or improved OSS compared with six months (six-month mean OSS 35.8 (SD 10.0); five-year mean OSS 40.1 (SD 9.1); r = 0.613). A Bland-Altman plot demonstrated a positive mean difference (3.3 OSS points (SD 7.92)) with wide 95% limits of agreement (-12.2 and 18.8 points). Conclusion: Timing of surgery did not affect OSS at any stage of follow-up, irrespective of age or fracture type. Most participants had maximum functional outcome at six months that was maintained at five years. These findings may help guide providers of trauma services on surgical prioritization. Cite this article: Bone Joint J 2020;102-B(1):33–41